KEPUTUSAN FIKTIF DALAM UPAYA ADMINISTRATIF TERHADAP KEPUTUSAN APARATUR SIPIL NEGARA - I Nengah Susrama; Putu Angga Pratama Sukma (Faculty of Law, Mahasaraswati University, Denpasar, 2019)
Substitution of Regional Head, there is usually a mutation / change of civil servants due to a cause due to internal factors that tend to be feudal culture. One of the efforts to resolve the transfer / replacement of civil servants by promoting administrative efforts towards the decree. When this administrative effort is carried out with a specified grace period, the Government Agency or Official does not respond / remain silent. This silence is the granting of the administrative effort (positive fictitious decision) of the applicant based on the Administrative Law of the Government.